Normalization of Overexpressed α-Synuclein Causing Parkinson's Disease By a Moderate Gene Silencing With RNA Interference - Masaki Takahashi; Mari Suzuki; Masashi Fukuoka; Nobuhiro Fujikake; Shoko Watanabe; Miho Murata; Keiji Wada; Yoshitaka Nagai; Hirohiko Hohjoh (Elsevier, 2015)
The α-synuclein (SNCA) gene is a responsible gene for Parkinson's disease (PD); and not only nucleotide variations but also overexpression of SNCA appears to be involved in the pathogenesis of PD. A specific inhibition against mutant SNCA genes carrying nucleotide variations may be feasible by a specific silencing such as an allele-specific RNA interference (RNAi); however, there is no method for restoring the SNCA overexpression to a normal level. Here, we show that an atypical RNAi using small interfering RNAs (siRNAs) that confer a moderate level of gene silencing is capable of controlling overexpressed SNCA genes to return to a normal level; named "expression-control RNAi" (ExCont-RNAi). ExCont-RNAi exhibited little or no significant off-target effects in its treated PD patient's fibroblasts that carry SNCA triplication. To further assess the therapeutic effect of ExCont-RNAi, PD-model flies that carried the human SNCA gene underwent an ExCont-RNAi treatment. The treated PD-flies demonstrated a significant improvement in their motor function. Our current findings suggested that ExCont-RNAi might be capable of becoming a novel therapeutic procedure for PD with the SNCA overexpression, and that siRNAs conferring a moderate level of gene silencing to target genes, which have been abandoned as useless siRNAs so far, might be available for controlling abnormally expressed disease-causing genes without producing adverse effects.